The Real Estate and Credit Bubble in Spain; Implications for Poland - Zbigniew Korzeb (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of this article is to establish whether the symptoms of an emerging housing bubble can be observed on the Polish market. The concept of this study is based on a comparison between economic, financial and demographic conditions at the time of the mortgage crisis in Spain and the current situation on the housing market and on the market of housing loans granted to households in Poland. An analysis of two economic indicators, (i) housing loans to households-to-GDP expressed in growth rates and (ii) rates of house price growth, does not indicate that a speculative bubble occurs in Poland now. This, however, does not mean that the conclusions drawn from the Spanish crisis cannot and should not have a bearing on the Polish market, especially in terms of potential consequences the crisis may have for the banking sector.